Fashion & literature research in Brazil: a quantitative profile, typology of aproaches, and methdological questions (Revista de Ensino em Artes, Moda e Design, 2020)
This article presents a quantitative analysis of fashion & literature research based on information about Brazilian theses and dissertations defended since 1987. It also points out and discusses the problems of the databases that gather information about these works and their consequences for investigations that use them for elab-ora- ting the “state of the art”.” Based on the analysis, the paper proposes and oper-ates a semiotic typology of approaches to fashion & literature researches. Studies that in- vestigate how literature uses fashion to talk about literature itself and socio-historical issues are predominant. Regarding the profile of the works, they are mainly developed in language/literature graduate programs at public universities in South-east Brazil.
Keywords: fashion and literature; state of the art; semiotic square